Dispersion analysis of development of tourism sector in the republic of Kazakhstan - Bissekov, A.; Bekbulatova, А.; Alimbekov, D. (KSU Publ., 2013)
For quite short time after obtaining independence, economic development of the Republic of Kazakhstan promptly goes forward. In the message of the president «Kazakhstan–2030», besides development of production of natural energy resources, special value is allocated the tourism industries. According to the concept of development of tourism in the Republic of Kazakhstan, it is capable to render three positive effects on national economy: first, to provide inflow of foreign currency and to have positive impact on such economic indicators as the balance of payments and cumulative export; secondly, helps to increase population employment; in the third, promotes development of infrastructure of the country. This research is devoted to study the branch of tourism in the Republic of Kazakhstan with use of the one-factorial dispersion analysis.
Қазақстан Республикасында туризм саласының дамуына дисперсиондық талдау
Дисперсионный анализ развития отрасли туризма в Республике Казахстан
Keywords: Republic of Kazakhstan; one-factorial dispersion analysis; tourism; Ronald Fischer; development strategy; gradations; influence of a factor; tourists flow; average size of a productive sign; tourist potential